The composition and optical characteristics of Marine aerosols - Yi Yizhe; Zhang Yiwen (E3S Web of Conferences)
Marine aerosols exert critical modulation of Earth’s climate system through dual mechanisms: direct alteration of radiative energy budgets and indirect regulation of cloud nucleation processes. This study conducted comprehensive molecular characterization of humic-like substances (HULIS) in marine aerosols through coordinated shipborne campaigns across the Yellow-Bohai Sea continuum. The analytical framework synergistically combines three-dimensional excitation-emission matrix fluorescence spectroscopy with multivariate chemometric processing techniques, enabling precise identification of chromophoric components and atmospheric transformation pathways. Analytical results demonstrate the competitive interplay between marine biogenic sources (phytoplankton-derived organic precursors) and terrestrial inputs (anthropogenic combustion products) in shaping coastal organic carbon profiles. Particularly, fluorescence spectral deconvolution revealed distinct molecular signatures corresponding to marine primary production and continental biomass burning. These findings quantitatively establish the non-negligible contribution of cross-regional atmospheric transport to coastal marine aerosols, highlighting the necessity for sustained interdisciplinary research efforts to resolve complex marine-atmosphere feedback mechanisms under changing climatic conditions.